Investigations of defect effect on dynamic compressive failure of 3D circular braided composite tubes with numerical simulation method. (March 2021) - Liu, Tao; Wu, Xianyan; Sun, Baozhong; Fan, Wei; Han, Wanli; Yi, Honglei
Abstract: This paper numerically investigated the effects of manufacturing defects and braiding angle on the impact compressive properties of three-dimensional (3D) carbon fiber/epoxy resin circular braided composite tubes. Based on the realistic geometrical architecture of 3D tubular braided preform, the full-size microstructural finite element analysis (FEA) models of the braided composite tubes with different braiding angles were established for the axial impact compression behavior at the split Hopkinson pressure bar apparatus. The manufacturing defects including fiber breakages and voids in the resin matrix were generated with Monte Carlo method in fiber tows and resin, respectively. The numerical results show the effects of defects in fiber tows and resin on the compressive strength, initial modulus, and failure strain of the braided composite tubes are both dependent on the braiding angle. The random defects have a negative influence on compressive failure mechanisms of the braided tubes. Comparing the failure morphologies of FEA models with experimental results, we found the non-ideal models containing random defects of appropriate content in fiber tows are more accurate than ideal models to simulate the dynamic compressive failure evolution process of 3D braided composite tubes. Highlights: The effect of defects on dynamic failure mechanism of three-dimensional (3D) circular braided composite tube was studied. Fiber breakage defects can cause the initial damage of 3D braided composite tubes. . Effects of different types of defect on 3D braided composite tubes are both related to the braiding angle. . Models including defects agree better with experimental results than ideal models.